Mineralization and formation conditions of metamorphic remobilization veins, Storliden VHMS deposit, Skellefte district, north Sweden - Uuttu, Petri (Helsingfors universitet, 2014)
The Paleoproterozoic volcanically hosted massive sulfide deposits of the Skellefte district, northern Sweden has been subjected to regional metamorphism in greenschist to amphibole facies conditions at 1.84 – 1.82 Ga, resulting in the remobilization of ore minerals and formation of ore-bearing quartz and sulfide veins. The aim of this project is to study the mineralogy and mineral chemistry of the Storliden VHMS deposit in the Skellefte district and determine the conditions the remobilization of ore minerals took place in. The sulfide-rich remobilization veins in the deposit consist of two types: ones composed mostly of pyrrhotite and chalcopyrite, and ones composed mostly of galena and bournonite, often as symplectitic intergrowths, with gudmundite and tetrahedrite occurring in notable amounts as well. Arsenopyrite and sphalerite were found in multiple veins of both types. Additionally, sulfide-poor quartz- and calcite veins occur in the deposit. There are also sulfide-bearing calcite veins that post-date the metamorphism, and were not included in this study. Sphalerite and chlorite from the veins both have lower Fe-content than same minerals in the massive ore and the host rock of the ore, respectively. Sphalerite form the veins also has a significantly higher Cd-content compared to the massive ore. The tetrahedrite from the veins also has a clearly different composition than in the massive ore, with considerably lower As-content and higher Fe/(Fe+Zn) ratio. Arsenopyrite geothermometry was used to determine that the remobilization took place at temperature of 325 – 480 °C, with mean T of 425 °C for the massive ore and 412 °C for the remobilization veins. The composition of sphalerite from the massive ore was used to determine that the pressure during metamorphism was 6.3 – 8.5 kbar, with mean of 7.5 kbar. Thermometric data obtained from chlorite in the quartz veins and the host rock of the ore indicates lower temperatures than the data from arsenopyrite, with mean T of around 200 °C or less for the veins and ...